2012
DOI: 10.12968/gasn.2012.10.9.30
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up care of stoma patients: a systematic literature review

Abstract: Each year approximately 21 000 people undergo stoma formation surgery in the UK ( High Impact Action Steering Group, 2010 ). Stoma care nurses are involved throughout the care pathway and the role of the stoma care nurse is fundamental in helping these patients adapt to living with a stoma, so they can resume a ‘normal’ life. There is much literature relating to adaption to living with a stoma and complications, but what evidence is available to support the provision of follow-up care for stoma patients? In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…We expect the difference of the self‐efficacy score between the two groups post‐test to be 15, with a standard deviation of 22 (110‐22/4), 80% power at a 5% level of significance (2‐sided), the minimum sample size is 35 per group; in total 70 (Machin et al . , Johnson ). Considering 20% dropout rate based on previous studies, we need a minimum of 84 patients (70 + 70 × 20%); 42 in each group.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We expect the difference of the self‐efficacy score between the two groups post‐test to be 15, with a standard deviation of 22 (110‐22/4), 80% power at a 5% level of significance (2‐sided), the minimum sample size is 35 per group; in total 70 (Machin et al . , Johnson ). Considering 20% dropout rate based on previous studies, we need a minimum of 84 patients (70 + 70 × 20%); 42 in each group.…”
Section: The Studymentioning
confidence: 99%
“…The sample size is calculated based on the expected difference of self-efficacy score using the Stoma Self-Efficacy Scale between the intervention and control group. We expect the difference of the self-efficacy score between the two groups post-test to be 15, with a standard deviation of 22 (110-22/4), 80% power at a 5% level of significance (2-sided), the minimum sample size is 35 per group; in total 70 (Machin et al 1997, Johnson 2012 dropout rate based on previous studies, we need a minimum of 84 patients (70 + 70 9 20%); 42 in each group. The process evaluation includes two parts: quantitative and qualitative.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…Lopez and Descerado et al identified that dialog between the patient and the healthcare team was a major tool for a better adaptation to life with an ostomy [21]. Several studies specify that education programs, social support, and follow-up before and after surgery are imperative factors [7,20,[22][23][24][25][26]. However, studies describing novel methods for consultations between the SCN and patients, and the manner in which patients provide feedback are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Emulating the development of consensus care for colorectal and urostomy surgery, the WOCN Society Consensus Conference on discharge criteria from home care for persons with new fecal or urinary diversions recommended that “… every person with an ostomy should have access to an ostomy nurse specialist in the ambulatory care setting who can provide ongoing education, counseling, and assistance with physical problems associated with the individual's ostomy.” The Wound, Ostomy, and Continence Nurse (WOCN) research literature emphasizes the importance of postdischarge care for stoma patients for physical, psychological, and social problems . From 20% to 71% of persons with ostomies experience complications such as pouch leakage and peristomal skin problems .…”
Section: Introductionmentioning
confidence: 99%
“…2 The Wound, Ostomy, and Continence Nurse (WOCN) research literature emphasizes the importance of postdischarge care for stoma patients for physical, psychological, and social problems. 3,4 From 20% to 71% of persons with ostomies experience complications such as pouch leakage and peristomal skin problems. 4 Peristomal skin problems affect one-third of colostomy patients and two-thirds of urostomy and ileostomy patients.…”
Section: Introductionmentioning
confidence: 99%